Digenis Akritas in the Byzantine Pottery : Iconographic and Literary Aspects (Fenestella. Inside Medieval Art, 2024)
This contribution aims to investigate the evolution and the characterisation of the iconography of the hero Digenis Acritas, a famous Byzantine literary figure. The hero's appearance on ceramic artefacts alone makes it possible to develop a discourse on the ultimate intentions of the artists and owners of such ceramics, by means of a cross-comprison of literary and historical sources from the mid-Byzantine period.
Keywords: Medieval Art; Byzantine Art; Byzantine monumental painting; Middle Byzantine Art; Medieval Iconography; pottery